Development of a quality assurance tool for intensive care units in Lebanon during the COVID-19 pandemic. (5th May 2022) - Halmin, Märit; Abou Mourad, Ghada; Ghneim, Adam; Rady, Alissar; Baker, Tim; Von Schreeb, Johan
Abstract: Background: During the coronavirus disease (COVID-19) pandemic, low- and middle-income countries have rapidly scaled up intensive care unit (ICU) capacities. Doing this without monitoring the quality of care poses risks to patient safety and may negatively affect patient outcomes. While monitoring the quality of care is routine in high-income countries, it is not systematically implemented in most low- and middle-income countries. In this resource-scarce context, there is a paucity of feasibly implementable tools to monitor the quality of ICU care. Lebanon is an upper middle-income country that, during the autumn and winter of 2020–1, has had increasing demands for ICU beds for COVID-19. The World Health Organization has supported the Ministry of Public Health to increase ICU beds at public hospitals by 300%, but no readily available tool to monitor the quality of ICU care was available. Objective: The objective with this study was to describe the process of rapidly developing and implementing a tool to monitor the quality of ICU care at public hospitals in Lebanon. Methods: In the midst of the escalating pandemic, we applied a systematic approach to develop a realistically implementable quality assurance tool. We conducted a literature review, held expert meetings and did a pilot study to select among identified quality indicators for ICU care that were feasible to collect during a 1-hour ICU visit. In addition, a limited set of the identified indicators that were quantifiable were specifically selected for a scoring protocol to allow comparison over time as well as between ICUs. Results: A total of 44 quality indicators, which, using different methods, could be collected by an external person, were selected for the quality of care tool. Out of these, 33 were included for scoring. When tested, the scores showed a large difference between hospitals with low versus high resources, indicating considerable variation in the quality of care. Conclusions: The proposed tool is a promising way to systematically assess and monitor the quality of care in ICUs in the absence of more advanced and resource-demanding systems. It is currently in use in Lebanon. The proposed tool may help identifying quality gaps to be targeted and can monitor progress. More studies to validate the tool are needed.